2013
DOI: 10.1017/jfm.2013.204
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar vortex-induced vibrations of a hanging string

Abstract: An experimental analysis of the vortex-induced vibrations of a hanging string with variable tension along its length is presented in this paper. It is shown that standing waves develop along the hanging string. The evolution of the Strouhal number St with the Reynolds number Re first follows a trend similar to what is observed for a circular cylinder in a flow for relatively low Reynolds numbers (32 < Re < 700). Second, the extracted mode shapes are self-similar : a rescaling of the spanwise coordinate by a se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In order to understand the dependence of the efficiency on ξ, the motion of the hanging cable is plotted inFigure 10 for three different damping parameters and = opt . For both small and high dampings, Figure 10 (a) and (c), the motion is characterized by mainly-stationary waves, as in the case of a fixed upper extremity [15]. The corresponding mode shape is actually very close to a zero-order Bessel function of the first kind, with either a free-end condition, y ( ) = 0 for small ξ, Figure 10 (a), or a fixed-end condition, y ( ) = 0 for high ξ, Figure 10 (c).…”
Section: Stationary and Traveling Wavesmentioning
confidence: 98%
See 3 more Smart Citations
“…In order to understand the dependence of the efficiency on ξ, the motion of the hanging cable is plotted inFigure 10 for three different damping parameters and = opt . For both small and high dampings, Figure 10 (a) and (c), the motion is characterized by mainly-stationary waves, as in the case of a fixed upper extremity [15]. The corresponding mode shape is actually very close to a zero-order Bessel function of the first kind, with either a free-end condition, y ( ) = 0 for small ξ, Figure 10 (a), or a fixed-end condition, y ( ) = 0 for high ξ, Figure 10 (c).…”
Section: Stationary and Traveling Wavesmentioning
confidence: 98%
“…The dimensionless cross-flow displacement y and time t are defined as in previous sections. Following Grouthier et al [15], the dimensionless spanwise coordinate is defined as z = Z/Z c where the characteristic length for the spanwise coordinate is Z c = m s g/m t ω 2 f . Given these characteristic dimensions, there are two dimensionless harvesting parameters.…”
Section: A Hanging Cable With a Localized Harvestermentioning
confidence: 99%
See 2 more Smart Citations
“…This analytical idea opened a new threshold for the interpretation of the frequency lock-in phenomenon. Besides, linear wake oscillator models have also been utilized to study VIV of slender flexible structures like cables and strings (Violette, De Langre & Szydlowski 2010;Grouthier et al 2013). The stability analysis results showed that linear models could capture a significant part of the underlying physics of the VIV phenomenon.…”
Section: Introductionmentioning
confidence: 99%